PERAN KELUARGA TERHADAP KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS TUMINTING KOTA MANADO - , Robin Dompas; , dr. Ova Emilia, M.Med, SpOG(K), Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The percentage of exclusive breastfeeding in Indonesia in 2008 and 2009 was 24.6% and 34.3%, respectively. In North Sulawesi Province in 2009 the percentage of exclusive breastfeeding was 54.8% and especially in Manado it reached 44.22%. Meanwhile, the percentage of exclusive breastfeeding in the working area of Tuminting Health Center in 2009 was 44.8%. The percentage was still low compared to the national target which was 80%. Factors affecting the low exclusive breastfeeding were mothers who interacted directly with the infants and other factors including family. Objective: To determine the relationship between family roles and exclusive breastfeeding in the working area of Tuminting Health Center, Manado. Methods: This was an observational analytic study using a cross sectional design with quantitative and qualitative approaches. The research was conducted at Tuminting health center of Manado Municipality from June to July 2011. The sample size was 100 mothers from families with babies aged 6-12 months meeting the inclusion criteria. The sampling technique was cluster sampling. Data collection used questionnaires with interviews. Analysis of the data used univariable, bivariable with chi square and multivariable with logistic regression, stratification, and qualitative analysis. Results: The good role of families had a greater prevalence of exclusive breastfeeding than the bad role of families (PR = 1.6